Nurses' knowledge, perception and practice toward discharge planning in acute care settings: A systematic review - Audai A. Hayajneh; Issa M. Hweidi; Milian W. Abu Dieh (Wiley, 2020)
Abstract Aim Discharge planning (DP) guides patients' transition to out‐hospital services. This systematic review investigates nurses' knowledge, perception and practices of discharge planning. Design We conducted a systematic review following PRISMA guidelines. Methods Search terms were used to identify research studies published between 1990-2020 across six databases: CINAHL, MEDLINE, PubMed, Complete Academic search, Science Direct and Google Scholar. A total of nine studies met the inclusion criteria. Results Nine articles revealed nurses' knowledge, perspectives and practices of discharge planning. Obstacles included low‐level knowledge of patients' activities and discharge; inability to define DP; debates over the timing of beginning, implementing and preparing discharge; patients and their family members' negative attitudes towards DP; and perceiving DP as excessive, time‐consuming paperwork for which the physician is responsible. Better time management during work improves DP in acute care settings.